Modified logistic differential equation of neutral type with time delay - Švitra, Donatas (Lietuvos matematikos rinkinys, 2003)
The following differential equation is considered:N(t) = rN[1 + a(1 − {N(t)}/K) − {N(t − h) + ρN(t − h)}/K].The stable periodic solution based on the bifurcation theory of that differential equation is constructed.